2000
DOI: 10.1046/j.1365-2184.2000.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Dilazep, a nucleoside transporter inhibitor, modulates cell cycle progression and DNA synthesis in rat mesangial cells in vitro

Abstract: The direct effects of the nucleoside transporter inhibitor dilazep on the cell cycle of mesangial cells have not before been investigated. The purpose of this study was to elucidate whether dilazep can inhibit the proliferation of mesangial cells and how it interferes with the cell cycle of these cells. DNA histograms were used and BrdUrd uptake rate was measured by flow cytometry. There was no significant difference in the cell numbers among the untreated group and the 10(-5) M, 10(-6) M or 10(-7) M dilazep-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…In this context, we demonstrated that dilazep treatment indeed attenuated glomerular sclerosis, suggesting that the vascular protection was observed throughout the systemic circulation. In addition, it has been well documented that dilazep, a nucleoside transporter inhibitor, behaves as an anti-platelet aggregatory drug and an oxygen-radical scavenger, and prevents the appearance of neurological symptoms and brain damage induced by ischemia and reperfusion (5)(6)(7)(8)(9)(10)(11). Unfortunately, we were unable to provide evidence that the scavenging effects of dilazep participated in the preservation of cognition.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In this context, we demonstrated that dilazep treatment indeed attenuated glomerular sclerosis, suggesting that the vascular protection was observed throughout the systemic circulation. In addition, it has been well documented that dilazep, a nucleoside transporter inhibitor, behaves as an anti-platelet aggregatory drug and an oxygen-radical scavenger, and prevents the appearance of neurological symptoms and brain damage induced by ischemia and reperfusion (5)(6)(7)(8)(9)(10)(11). Unfortunately, we were unable to provide evidence that the scavenging effects of dilazep participated in the preservation of cognition.…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, this drug uniquely behaves in vitro as an oxygen-radical scavenger (7). Such multifactorial actions are believed to attenuate mesangial cell proliferation or glomerular injury in immunoglobulin A (IgA) nephropathy (8)(9)(10). More interestingly, dilazep is reported to prevent the appearance of neurological symptoms and brain damage induced by ischemia following carotid artery occlusion and reperfusion, probably through suppression of lipid peroxidation (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inhibiting nucleoside transporter activity does not typically block cell cycle progression at G 2 /M. For example, Sakumura et al (36) showed that dilazep, an adenosine uptake inhibitor, blocks cells at both G 1 and S phase. Thus, the unique effects of Ir(III)-PPY nucleoside on cell cycle progression prompted us to further investigate its activity against KB3-1 cells synchronized at G 1 by treatment with L-mimosine (37).…”
Section: Non-invasion Detection Of Ir(iii)-ppy Nucleoside Uptake Via mentioning
confidence: 99%